2021
DOI: 10.1186/s12870-021-02962-2
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome dynamic landscape underlying the improvement of maize lodging resistance under coronatine treatment

Abstract: Background Lodging is one of the important factors causing maize yield. Plant height is an important factor in determining plant architecture in maize (Zea mays L.), which is closely related to lodging resistance under high planting density. Coronatine (COR), which is a phytotoxin and produced by the pathogen Pseudomonas syringae, is a functional and structural analogue of jasmonic acid (JA). Results In this study, we found COR, as a new plant grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 121 publications
0
8
1
Order By: Relevance
“…For instance, a set of genes influence plant height by regulating gibberellin (GA) biosynthesis and transport, including dwarf1, dwarf3, dwarf plant 8, and dwarf plant 9 ( Spray et al, 1996 ; Sakamoto et al, 2004 ; Cui et al, 2012 ) . Studies have also revealed that jasmonic acid (JA) can affect plant height via complex phytohormone crosstalk with GA and auxin ( Ren et al, 2021 ) . Furthermore, NAC transcription factors were shown to enhance maize stalk lodging resistance by directly regulating genes involved in cell wall biosynthesis ( Ren et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, a set of genes influence plant height by regulating gibberellin (GA) biosynthesis and transport, including dwarf1, dwarf3, dwarf plant 8, and dwarf plant 9 ( Spray et al, 1996 ; Sakamoto et al, 2004 ; Cui et al, 2012 ) . Studies have also revealed that jasmonic acid (JA) can affect plant height via complex phytohormone crosstalk with GA and auxin ( Ren et al, 2021 ) . Furthermore, NAC transcription factors were shown to enhance maize stalk lodging resistance by directly regulating genes involved in cell wall biosynthesis ( Ren et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Compared to traditional sequencing methods, RNA-seq technologies offer several key advantages, such as low cost, high throughput, and high sensitivity. Furthermore, RNA-Seq provides us convenience in detecting transcriptomic changes under certain environments and enables us to identify gene expression profiles in a specific manner ( Ren et al, 2021 ). Meanwhile, metabolomic profiling is being used to detect the differential abundance of metabolites at a global level and also provides useful contributions to molecular genetics studies ( Zhao et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Among these genes, ZmBZR1 showed the highest expression level ( Figure 3 c). Coronatine (COR), a functional and structural analog of jasmonic acid (JA), can improve maize lodging resistance by inhibiting ninth internode elongation [ 23 ]. The meristem (M, basal 0–1 cm between internode) and elongation regions (E, basal 1–2 cm between internode) of the ninth internode were collected for RNA-seq.…”
Section: Resultsmentioning
confidence: 99%
“…RNA extraction and library preparing proceeded according to the method of Ren et al [ 21 ]. Total RNA was extracted using Trizol (Invitrogen, Carlsbad, CA, USA) based on the manual.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have shown that COR can regulate maize morphogenesis and promote maize growth at the seedling stage [ 20 ]. It can also improve lodging resistance and enhance maize resistance to low temperature and drought [ 21 , 22 , 23 ]. However, it has not been reported that COR can improve pest resistance of maize at the seedling stage.…”
Section: Introductionmentioning
confidence: 99%